Evaluating the Safety and Efficacy of Intravenous Thrombolysis in Acute Ischemic Stroke Patients Without Perfusion Deficit: A Retrospective Analysis - Alhaj Omar, Omar; Gerner, Stefan T.; Alikevitch, Slava; Hamzic, Samra; Viard, Maxime; Mrochen, Anne; Böttger, Priyanka; Juenemann, Martin; Braun, Tobias; Justus Liebig University Giessen (My University, 2025)
Background/Objectives: Acute ischemic stroke (AIS) remains a major cause of morbidity and mortality worldwide. Although advanced imaging modalities, such as CT perfusion (CTP), are increasingly being used in clinical decision-making, the necessity and added value of perfusion imaging prior to intravenous thrombolysis (IVT) within early time windows remains uncertain. We aim to evaluate the safety and functional outcomes of IVT in AIS patients without perfusion deficits on CTP. We question the requirement of perfusion mismatch for IVT eligibility and hypothesize that IVT is safe and beneficial even in the absence of a perfusion deficit. Methods: A retrospective analysis was conducted using data from the Giessen Stroke Registry, focusing on AIS patients who underwent CTP imaging and received IVT between 01/2018 and 12/2020. Patients who underwent endovascular therapy were excluded. Clinical data, including demographics, National Institutes of Health Stroke Scale (NIHSS) scores, modified Rankin Scale (mRS) scores, and complications, were collected. Patients were dichotomized based on the presence of perfusion lesions and compared in terms of efficacy outcomes (i.e., NIHSS or mRS improvement during the hospital stay) and safety outcomes (i.e., post-thrombolytic hemorrhagic complications). Results: Of the 89 AIS patients with available CTP data who received IVT, 34 (38%) had a perfusion deficit and 55 (62%) did not. There were no significant differences between the groups in terms of hemorrhagic complications or functional outcomes at discharge (NIHSS and mRS). Clinical improvement from admission to discharge was similar in both groups. Conclusions: Our findings suggest that IVT is safe and clinically effective even in AIS patients without detectable perfusion deficits on CTP within the standard therapeutic window. These results support current guideline recommendations that do not mandate perfusion imaging for early presenters. Routine use of CTP in this context may be of limited clinical utility and could unnecessarily delay treatment or introduce additional risks in the first 4.5 h.
Keywords: ddc:610